Factors Influencing Autoimmune Thyroid Disease - Nada Fadhil Abbas; Maad Naser Shaker (American Journal of Biology and Natural Sciences, 2025)
Autoimmune thyroid disease (AITD) are among the most common diseases in recent times. Their causes and symptoms vary from one person to another. The main cause may be an immune or acquired disorder. Therefore, this article aims to focus on the causes that lead to thyroiditis, hyperactivity and lethargy. Most of these causes are known and common, and recovery can be achieved when the main cause is known. The infection may be diagnosed based on the causes in addition to the apparent symptoms and using common diagnostic methods such as X-rays, ultrasound, and laboratory testing of thyroid hormones.